Human cultured IMR-32 neuronal-like and U87 glial-like cells have different patterns of toxicity under fluoride exposure. - Bruna Puty (Public Library of Science (PLoS), 2021)
Background Fluoride (F) is a naturally exists in nature but several studies have indicated it as an environmental toxicant to all leaving beings. Human F exposure has increased over the years since this ion has been used by industry on foods, beverages, toothpastes and on water supply. Although F is safe at optimal concentrations in water supply, human exposure to high levels could trigger neurofunctional deficits. Materials and methods In this study, human glial-like (U87) and neuronal-like (IMR-32) cells lineages were used to access F toxicity and CNS cell sensibility on both cell facing the same protocol. Cells were exposed to F over 3, 5 and 10 days on two different F concentrations. Fluoride exposed cells were evaluated by standard toxicity assays to cell viability, apoptosis, necrosis and general cell metabolism. Oxidative stress parameters were evaluated by ATP and ROS levels, lipid peroxidation, GSH/GSSG ratio and comet assay. Results No changes were observed in IMR-32 at any given time while after 10 days of exposure to 0.22μg/mL, U87 glial-like cells showed signs of toxicity such as decreased cell viability by necrosis while general cell metabolism was increased. Oxidative stress parameters were next evaluated only on U87 glial-like cells after 10 days of exposure. F induced a decrease on ATP levels while no changes were observed on reactive oxygen species and lipid peroxidation. GSH/GSSG ratio was decreased followed by DNA damage both on 0.22μg/mL F. Conclusions Our results suggest an important differential behavior of the distinct types of cells exposed to the different fluoride concentrations, pointing that the U87 glial-like cells as more susceptible to damage triggered by this ion.